2010
DOI: 10.1073/pnas.1005743107
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA traps promote thrombosis

Abstract: Neutrophil extracellular traps (NETs) are part of the innate immune response to infections. NETs are a meshwork of DNA fibers comprising histones and antimicrobial proteins. Microbes are immobilized in NETs and encounter a locally high and lethal concentration of effector proteins. Recent studies show that NETs are formed inside the vasculature in infections and noninfectious diseases. Here we report that NETs provide a heretofore unrecognized scaffold and stimulus for thrombus formation. NETs perfused with bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
2,148
0
46

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,058 publications
(2,238 citation statements)
references
References 41 publications
44
2,148
0
46
Order By: Relevance
“…27 The NETting process could also have a predominant role in the generation of a beneficial extracellular matrix by delivering proteinases and could also favor the release of inflammatory and angiogenic factors. For example, NETs have been shown to contain and activate matrix metalloproteinases, 28 preserve the enzymatic activity of elastase 29 and recruit platelets, 30 important cells for angiogenesis. 31 Neutrophils were described to suppress the cytotoxic CD8 C antitumoral response, which is associated with the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…27 The NETting process could also have a predominant role in the generation of a beneficial extracellular matrix by delivering proteinases and could also favor the release of inflammatory and angiogenic factors. For example, NETs have been shown to contain and activate matrix metalloproteinases, 28 preserve the enzymatic activity of elastase 29 and recruit platelets, 30 important cells for angiogenesis. 31 Neutrophils were described to suppress the cytotoxic CD8 C antitumoral response, which is associated with the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of NETs and histones to influence the coagulation cascade and actually initiate venous thrombosis8, 133, 134 is the most recent detail in the emerging field of NETosis research. Clinically, circulating nucleosomes are independent prognostic markers of disseminated intravascular coagulopathy (DIC)135 and some countries, notably Japan, are actively promoting the use of anticoagulants as histone detoxification agents in DIC 136.…”
Section: Molecular Basis Of Histone‐related Cellular and Tissue Injurymentioning
confidence: 99%
“…More recently, controlled histone degradation has been described in neutrophils leading to chromatin decondensation and release of genomic DNA laced with granular proteins as neutrophil extracellular traps (NETs) 6, 7. These meshwork‐like structures promote intravascular thrombosis,8 limit spread of microorganisms, encourage cancer metastasis9 and cause direct injury to adjacent cells 10…”
Section: Introductionmentioning
confidence: 99%
“…31 In an ex-vivo study, NETs have been shown to stimulate platelet binding and aggregation and induce formation of red blood cell rich thrombus. 32 Recently, loss-of-function mutations in the CECR1 (cat eye syndrome chromosome region, candidate1) gene encoding adenosine deaminase 2 (ADA2) have been reported to be associated with inflammatory vasculopathy. 33,34 It is unclear whether this new subset of inflammatory vasculitis caused by genetic mutations is associated with venous thrombosis.…”
Section: Mechanisms Linking Inflammation and Venous Thrombosismentioning
confidence: 99%